Opportunities in the Acute Care Setting for Infectious Diseases/Hospitalist Patient Co-Management. (4th October 2017) - Gupta, Siddhi; Bansal, Amit; Newman, Eric; Martin, Stanley
Abstract: Background: In an inpatient setting, Infectious Diseases (ID) physician care may lead to lower mortality rates and readmissions. When consultation is performed earlier in the admission, outcomes may even be better. The model of individual consultative care that relies on primary services calling specialists to give recommendations can lead to missed opportunities for optimal diagnostic testing and antimicrobial utilization. Having ID specialists involved in the care of the hospitalized patient from the time of admission creates a unique opportunity for timely intervention that could have long-ranging effects. Methods: Patients admitted to four of the non-teaching hospitalist services at Geisinger Medical Center over two separate weeks included automatic ID evaluation within 24 hours of admission. The ID physician reviewed the chart and records of each admission to determine whether the patient was being treated for an infection. Any potential ID-related interventions identified upon initial evaluation were recorded by the ID physician. Patients were excluded if formal ID consultation was requested. Results: A total of 85 patients were admitted during the study and 84 were included for review. Forty-five (53.6%) were admitted for a total of 48 infection-related reasons and another 17 (20.2%) were found to have incidental infection-related findings. Seven patients had requests for formal ID consultation placed (8.3%). Of the remaining primary ID diagnoses on admission, 33 were accurate by ID physician assessment (68.8%) and empiric therapy was appropriate in 29 (60.4%). Of the incidental infection-related diagnoses, 12 (70.5%) were considered accurate and empiric therapy was appropriate in 12 (70.5%). Among primary ID diagnoses, 60 diagnostic testing opportunities and 25 potential therapeutic improvements were identified (Figures). Conclusion: Despite the limitations of relying on medical records alone, when done in real time, a large number of opportunities exist to optimize diagnostic testing and antimicrobial use in the acute care setting. As healthcare moves away from fee-for-service models to population health, the concept of an ID physician/hospitalist co-management model of inpatient care should be explored further. Disclosures: All authors: No reported disclosures.